Comparison of efficacy of telmisartan with losartan in patients of essential hypertension with cognitive impairment - Puram, Nitin Natthuji; Karande, Vitthal Baburao; Ramanand, Jaiprakash Bharma; Ramanand, Sunita Jaiprakash; Halasawadekar, Nimish Ravindra; Bhosale, Rama Rangnathrao (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Hypertension can lead to mild to moderate alteration in the brain structure and function including cognitive functions impairments. Many first line antihypertensive drugs are devoid of producing significant improvement in cognitive functions; in fact some of them worsen cognitive function. Data suggests that angiotensin II receptor antagonist slows the progression of cognitive impairment associated with hypertension. Hence present study was planned to compare the efficacy of telmisartan with losartan in hypertensive patients with cognitive impairment. Methods: Prospective, randomized, single blind, comparative study was conducted for period of 24 weeks. Study population was enrolled into two groups: group A (losartan 50 mg) and group B (telmisartan 20 mg). Cognitive functions were assessed by mini mental status examination and trail making test part-A. Qualitative data were analysed by using “Fischer’s test” and quantitative data was analysed by using “t test”. Results: Baseline clinical characteristics of patients receiving losartan and telmisartan did not show significant difference Telmisartan was as effective as losartan in lowering systolic and diastolic blood pressure in patients of essential hypertension. Increase in mini mental status examination score appeared similar in both groups and there was no statistically significant difference (p>0.05) between the two groups at 12 and 24 weeks of therapy. Reduction in trail making test part A score was slightly more among patient receiving losartan but on comparison of two groups reduction in trail making test part A score was not statistically significant (p>0.05) at 12 and 24 weeks of therapy. Conclusions: Telmisartan is as effective as losartan in controlling blood pressure and improving cognitive function in hypertensive patients with cognitive impairment.